Reliability-monitoring data coupled model for concrete slab safety evaluation of CFRD and its engineering application. (January 2022) - Li, Junru; Lu, Xiang; Chen, Jiankang; Yang, Songlin; Kuang, Chufeng; Fan, Yong; Hu, Kongzhong
Abstract: The concrete-faced rockfill dam (CFRD) is one of the widely constructed dam types, the concrete slab is the key anti-seepage structure of CFRD, and its safety directly affects the safety of the dam. In view of the traditional reliability analysis methods are complicated to calculate and cannot assess concrete slab cracking risk in real-time. In this paper, through the analysis of the response mechanism of slab stress and dam deformation, the coupling relationship between the reliability of concrete slab and monitoring data is revealed. Considering the randomness of the material parameters of CFRD, the limit state functions of concrete slab cracking are established by the response surface method (RSM). The accurate numerical simulation of the construction and operation process of CFRD is realized through the back analysis, then the time-variant reliability calculation of the concrete slab is realized. By analyzing the correlation between concrete slab reliability and some key factors such as dam displacement, water level, and time, a coupled evaluation model of reliability and monitoring data is proposed. Houziyan CFRD is selected as an example, the engineering application shows that the simulation relative error by using this coupled evaluation model is less than 5.0%, this model has the advantages of high efficiency, good precision, and strong applicability. The real-time reliability analysis of the concrete slab is realized and a new method for prediction and early warning of concrete slab cracking of CFRDs is provided.